TUYỂN CHỌN CHỦNG NẤM MỐC ASPERGILLUS sp CÓ KHẢ NĂNG SINH TỔNG HỢP GLUCOOXYDAZA CAO - Hường, Nguyễn Thúy; Hiển, Ngô Tiến; Thu, Nguyễn Minh; Thủy, Khuất Thị; Thanh, Đàm Lam; Châu, Trần Thị (Vietnam Journal of Science and Technology, 2012)
SELECTION THE STRAIN OF ASPERGILLUS sp FOR BIOSYNTHESIS OF GLUCOSE OXYDASE ENZYME The glucose oxydase enzyme (GOx) (EC 1.1.3.4) binds to beta-D-glucopyranose (a hemiacetal form of the six-cacbon sugar glucose) and aids in breaking the sugar down into its metabolites. GOx is a dimeric protein that catalyzes the oxidation of beta-D-glucose into D-glucono – 1,5- lactone (which then hydrolyzes to gluconic acid) using molecular oxygen and releasing hydrogen peroxide. GOx can be used in the removal of either glucose or oxygen from foodstuffs in order to improve their storage capability. Among the 22 strains of Aspergillus in the National Food industrial Culture Collection of Microorganism of Food Industries Research Institute (FIRI), 6 strains coded as 9.4; 9.74; 1922F1; 1923F2; A1; A20 showed high glucose oxydase enzyme synthesis activity. The strain A. niger 9.4 and A20 had the highest glucose oxydase enzyme synthesis activity were selected to test forming aflatoxin. Both of them were negative with aflatoxin B1, B2, G1 and G2 on the test medium. The strain A. niger 9.4 synthesized GOx enzyme with the highest content (32.9 U/g of the biomass) was selected for further study to product glucose oxydase enzyme.